Beyond Eurafrica: Encounters in a Globalized World - (:unkn) unknown (My University, 2018)
Of course, the obvious question when speaking about European-African relationships is that of enduring colonial legacies, which can be apprehended at various scales depending on the phenomena observed, the assumptions made, and the disciplinary or epistemological perspectives that are privileged. In an effort at interdisciplinarity, it is the richness of research paths taken by Africanist scholars that this feature proposes, from a consideration of Europe and Africa as coherent entities on the global stage to tailored non-monolithic approaches of those entangled and hybrid spaces. Together, the works gathered here emphasize not only the validity of supranational level inquiries into the interrelatedness of a “Europe” with an “Africa,” but they also underscore the myriads bilateral intertwinings between one among many European nations and one among many African nations, as well as between individuals or specific groups. While the character of these connections almost always rests on colonial history and post-colonial geo-political asymmetric arrangements, they also reveal that the bonds between the peoples or Europe and the peoples of Africa did not end with independences, and that they subsist not only through political and economic flows, but also through flows of people, ideas, and cultures.
Keywords: African Research